Microhematuria as an Indicator of Significant Abdominal Injury. Issue 12 (December 2021) - Ohana-Sarna-Cahan, Lea; Levin, Yonatan; Gross, Itai; Hassidim, Ayal; Yuval, Jonathan Benjamin; Hess, Amit; Bala, Miklosh; Hashavya, Saar
Abstract : Background and Objectives: Trauma is one of the leading causes of morbidity and mortality in the pediatric population. In many centers, microhematuria is used as a screening tool for the presence of significant abdominal injury and as an indication for further imaging. Our objective was to evaluate the role of microhematuria by dipstick as an indicator of significant abdominal injury in children. Methods: A retrospective review of children aged 0 to 16 years admitted for a motor vehicle accident or a fall from 2007 to 2017 who had urinalyses performed. Results: The charts of 655 children were reviewed. Microhematuria was found in 100 children, of whom 49 (49%), 28 (28%), and 23 (23%) had small, moderate, and large amounts of hematuria, respectively. Of the children who had microhematuria, 41 underwent a computed tomography scan. Positive findings were recorded in 16 (39%) of these patients. There was a clear association between microhematuria as detected by the urine dipstick and a significant finding on the computed tomography scan ( P = 0.002). The sensitivity of microhematuria for significant abdominal pathology on imaging was 66.6% and the specificity was 68.3% (positive predictive value, 39%; negative predictive value, 87.1%). Microhematuria was associated with increased length of stay in the hospital ( P < 0.001), surgical interventions ( P = 0.036), and admission to the pediatric intensive care unit ( P < 0.001). Conclusions: The diagnostic role of dipstick urine analysis in the assessment of intra-abdominal injury has low sensitivity and specificity. Nevertheless, it is still a valuable screening tool for the evaluation of the severity of injury.